Freeze–thaw processes correspond to the protection–loss of soil organic carbon through regulating pore structure of aggregates in alpine ecosystems - R. Wang; R. Wang; X. Hu; X. Hu (SOIL)
Seasonal freeze–thaw processes alter soil formation and lead to changes in soil structure of alpine ecosystems. Soil aggregates are basic soil structural units and play a crucial role in soil organic carbon (SOC) protection and microbial habitation. However, the impact of seasonal freeze–thaw processes on pore structure and their impact on SOC fractions have been overlooked. This study characterized the pore structure and SOC fractions of soil aggregates of the unstable freezing period, stable frozen period, unstable thawing period and stable thawed period in typical alpine ecosystems via a dry-sieving procedure, X-ray computed tomography scanning and elemental analysis. The results showed that pore networks of 0.25–2 mm aggregates were more vulnerable to seasonal freeze–thaw processes than those of >2 mm aggregates. The freezing process promoted the formation of >80 µm pores of aggregates. The total organic carbon, particulate organic carbon and mineral-associated organic carbon contents of aggregates were high in the stable frozen period and dropped dramatically in the unstable thawing period, demonstrating that the freezing process was positively associated with SOC accumulation, while SOC loss featured in the early stage of thawing. The vertical distribution of SOC of aggregates was more uniform in the stable frozen period than in other periods. Pore equivalent diameter was the most important structural characteristic influencing SOC contents of aggregates. In the freezing period, the SOC accumulation might be enhanced by the formation of >80 µm pores. In the thawing period, pores of <15 µm were positively correlated with SOC concentration. Our results revealed that changes in pore structure induced by freeze–thaw processes could contribute to SOC protection of aggregates.